2007
DOI: 10.1016/j.neuropsychologia.2005.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Auditory motion affects visual biological motion processing

Abstract: The processing of biological motion is a critical, everyday task performed with remarkable efficiency by human sensory systems. Interest in this ability has focused to a large extent on biological motion processing in the visual modality (see, for example, Cutting, J. E., Moore, C., & Morrison, R. (1988). Masking the motions of human gait. Perception and Psychophysics, 44(4),[339][340][341][342][343][344][345][346][347]. In naturalistic settings, however, it is often the case that biological motion is defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
47
1
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 26 publications
5
47
1
1
Order By: Relevance
“…Previous investigations have demonstrated audio-visual facilitation in lower-order tasks; detection of biological motion (Burr et al 2007), and also in discriminating the direction in which a point-light Wgure moves (Brooks et al 2007;Meyer and Wuerger 2007). The Wndings we report here are some evidence that the same types of interactions now seem to aVect also representational qualities of Wgures in motion.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous investigations have demonstrated audio-visual facilitation in lower-order tasks; detection of biological motion (Burr et al 2007), and also in discriminating the direction in which a point-light Wgure moves (Brooks et al 2007;Meyer and Wuerger 2007). The Wndings we report here are some evidence that the same types of interactions now seem to aVect also representational qualities of Wgures in motion.…”
Section: Discussionmentioning
confidence: 98%
“…With that in mind, it is perhaps surprising that only recently the multisensory interactions have become a focus within the biological motion literature. For example, we recently reported that auditory information predictably inXuences vision-based biological motion sensitivity (Brooks et al 2007). More speciWcally, auditory motion cues seem to aVect observers' abilities to detect PLWs in noisy visual environments.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of audiovisual perception of biological motion similarly have proposed that naturally relevant (and/or familiar) dynamics facilitate perceptual integration and detection (Brooks et al, 2007;Saygin et al, 2008;Schouten et al, 2011). These studies have shown that adding auditory information that is consistent (congruent) with a possible interpretation of biological motion within patterns of moving lights increases the likelihood that a person will detect biological motion.…”
Section: Perceptual and Decision-related Contributions To Audiovisualmentioning
confidence: 99%
“…Strong cross-modal interaction exists between the auditory and visual modalities (Alais et al, 2010;Brooks, van der Zwan, Billard, Petreska, Clarke, & Blanke, 2007;SotoFaraco, & Kingstone, 2004;Wuerger, Hofbauer, & Meyer, 2003). For example, when a sound is played in the dark, perception of the origin of the sound can be biased toward the location of a concurrent flash-the spatial ventriloquist illusion (Alais & Burr, 2004b;Bertelson & Aschersleben, 1998;Bertelson & Radeau, 1976).…”
mentioning
confidence: 99%
See 1 more Smart Citation